2021
DOI: 10.1029/2020gl092308
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐Driven Characteristics of Sea‐Land Breezes Over the Globe

Abstract: Sea‐land breeze (SLB) is a critical component of the urban environment, wind power utilization, fishing industry, etc. along coastal areas where 40% world population live. Surrounding meteorological factors like the background wind field, temperature, and cloud fraction have all been reported to greatly impact SLB evolution. However, a climatological understanding of SLBs over the globe remains limited. This study quantifies the significance of SLBs under different climates over the globe for the first time, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Here we showed a decoupled variability and trends between SB speeds and gusts, which represents a nding never reported before for local winds. Actually, our results also showed that the understanding of SB changes is challenging, as many local factors can occur at the same time and drivers differ between mean and gust speeds(Miller et al 2003;Shen et al 2019Shen et al , 2021b. A speci c discussion of the principal ndings of this research follows:4.1 Increased SB occurrence due to anticyclonic activity and other related large-scale dynamicsThe overall increase in the annual SB occurrence is in agreement with some global analyses (Jiang et al2010; Perez et al 2017; Shen and Zhao 2020), but this trend may not be a widespread phenomenon (Pazandeh-Masouleh et al 2019; Shen et al 2019).…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…Here we showed a decoupled variability and trends between SB speeds and gusts, which represents a nding never reported before for local winds. Actually, our results also showed that the understanding of SB changes is challenging, as many local factors can occur at the same time and drivers differ between mean and gust speeds(Miller et al 2003;Shen et al 2019Shen et al , 2021b. A speci c discussion of the principal ndings of this research follows:4.1 Increased SB occurrence due to anticyclonic activity and other related large-scale dynamicsThe overall increase in the annual SB occurrence is in agreement with some global analyses (Jiang et al2010; Perez et al 2017; Shen and Zhao 2020), but this trend may not be a widespread phenomenon (Pazandeh-Masouleh et al 2019; Shen et al 2019).…”
mentioning
confidence: 84%
“…Despite being a widely studied phenomenon through numerical simulations (Drobinski et al 2018), cases-study (Cana et 2019; Shen and Zhao 2020, Shen et al 2021aShen et al , 2021b. In fact, there is no study examining how changes in SB in uence the seasonal trends and variability of winds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…bareland, forest and cropland). With surface properties such as surface albedo, surface roughness, Bowen ratio (sensible heat flux divided by latent heat flux) (Li et al 2019), the underlying surface dynamics and thermodynamics exchange energy, momentum, and substance with the atmosphere to influence the global and regional climate (Sellers et al 1997, Shepherd 2006, Lee et al 2011, Sterling et al 2013, Zhao et al 2014, Findell et al 2017, Shen and Zhao 2020, Shen et al 2021. As a result, surface temperature responds to land surface energy dissipation (Juang et al 2007, Luyessart et al 2014.…”
Section: Introductionmentioning
confidence: 99%